2021
DOI: 10.1021/acs.est.0c06633
|View full text |Cite
|
Sign up to set email alerts
|

Biological Reduction of a U(V)–Organic Ligand Complex

Abstract: Metal-reducing microorganisms such as Shewanella oneidensis MR-1 reduce highly soluble species of hexavalent uranyl (U(VI)) to less mobile tetravalent uranium (U(IV)) compounds. The biologically mediated immobilization of U(VI) is being considered for the remediation of U contamination. However, the mechanistic underpinnings of biological U(VI) reduction remain unresolved. It has become clear that a first electron transfer occurs to form pentavalent (U(V)) intermediates, but it has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Several studies including noncrystalline U(IV) with organic ligands have previously used the method. 33 , 50 …”
Section: Methodsmentioning
confidence: 99%
“…Several studies including noncrystalline U(IV) with organic ligands have previously used the method. 33 , 50 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, we expect that little to no active biomass will be present, especially given the removal of the electron donor. 61 After washing, the noncrystalline U(IV) product was resuspended in NaCl and MOPS. Previous work has shown that this product is stable in a simple buffered medium (e.g., PIPES−bicarbonate 38 ), indicating that these washing steps do not alter the U(IV) speciation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the proposed PEC method opens a new avenue toward the facile synthesis of U(V), an often “overlooked” U oxidation state. U(V) chemistry is important for elucidating the biogeochemical behaviors of U in the environment and understanding the properties of the f electrons of actinide ions ( Molinas et al., 2021 ; Chen et al., 2005 ). And a facile U(V) synthesis method is useful for assisting future studies on the U(V) chemistry.…”
Section: Discussionmentioning
confidence: 99%